Model Wisata Edukasi Berbasis Animal Welfare: Analisis Implementasi di Pusat Latihan Gajah Indonesia - Widyawati, Tri; Wulandari, Christine; Kaskoyo, Hari; Hilmanto, Rudi (MAKILA, 2025)
Indonesia has a place to train elephants called the Elephant Training Center/PLG. The forerunner of PLG in Indonesia is in Lampung, precisely in Way Kambas National Park/TNWK. Way Kambas National Park is a conservation area in Lampung Province based on the Decree of the Minister of Forestry Number 670/Kpts-II/1999 dated August 26, 1999, with an area of 125,631.31 ha. The purpose of this study was to obtain data and information on the implementation of educational-based tourism, to analyze the implementation of educational-based tourism in PLG (Indonesia) and to provide a new paradigm on elephant management based on the principle of Animal welfare as a consideration in determining PLG (Indonesia) policies in the future. The method used is the literature review research method. Viewed from the perspective of the existence of veterinarians in PLG Indonesia, educational elephant tourism with an Animal welfare approach can be implemented. Educational elephant tourism with an Animal welfare approach is a discourse that can be implemented in PLG throughout Indonesia related to the availability of facilities and medical personnel. The concept of educational tourism with an Animal welfare approach provides a new paradigm to tourists regarding the concept of tourism with an attraction object in the form of elephants with a new touch, namely utilizing elephants elegantly without the impression of elephant exploitation. The use of elephants as an attraction object with an exploration pattern of all natural elephant activities that are modified as a result of a collection of wild elephant taming methods to become tame which are referenced from the Thai method can be developed through the concept of educational tourism with an Animal welfare approach.